2013
DOI: 10.1177/1741143213499259
|View full text |Cite
|
Sign up to set email alerts
|

Exploring ethical dilemmas for principals arising from role conflict with school counsellors

Abstract: Acting in the best interests of students is central to the moral and ethical work of schools. Yet tensions can arise between principals and school counsellors as they work from at times opposing professional paradigms. In this article we report on principals’ and counsellors’ responses to scenarios covering confidentiality and the law, student/teacher relationships, student welfare and psychological testing of students. This discussion takes place against an examination of ethics, ethical dilemmas and professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
(78 reference statements)
0
12
0
Order By: Relevance
“…Researchers have suggested that a strong relationship between a principal and school counselor helps principals to understand the school counselor's role more clearly, possibly leading to greater programmatic alignment, improved services, and higher student achievement (Dahir et al, 2011). Pointing to role and foci differences, Kimber and Campbell (2013) found that discrepancies existed between principals' and school counselors' interpretations of ethical dilemmas and recommended that a stronger relationship between the two roles could assist in aligning viewpoints. Differences on programmatic views between school counselors and principals were also found by McCotter and Cohen (2013).…”
Section: Feautured Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have suggested that a strong relationship between a principal and school counselor helps principals to understand the school counselor's role more clearly, possibly leading to greater programmatic alignment, improved services, and higher student achievement (Dahir et al, 2011). Pointing to role and foci differences, Kimber and Campbell (2013) found that discrepancies existed between principals' and school counselors' interpretations of ethical dilemmas and recommended that a stronger relationship between the two roles could assist in aligning viewpoints. Differences on programmatic views between school counselors and principals were also found by McCotter and Cohen (2013).…”
Section: Feautured Researchmentioning
confidence: 99%
“…The widespread influence of the principal-school counselor relation-ship is well supported. The topics explored relate relationship quality to school counselor burnout (Gündüz, 2012;Wilkerson & Bellini, 2006), efficacy (Atici, 2014), job satisfaction (Clemens et al, 2009;Kolodinsky et al, 2009;Pyne, 2011), role conflict and ambiguity (Cervoni & Delucia-Waack, 2011;Dahir et al, 2011;Kimber & Campbell, 2013;Zalaquett & Chatters, 2012), and role definition (Amatea & Clark, 2005;Armstrong et al, 2010;Dodson, 2009;Dollarhide et al, 2007;Fitch, Newby, Ballestero, & Marshall, 2001;Henderson, 1999;Janson et al, 2008;Kimber & Campbell, 2013;Kolodinsky et al, 2009;MacDonald et al, 2008;Niebuhr et al, 1999;Perera-Diltz & Mason, 2008;Ponec & Brock, 2000;Pyne, 2011;Wilmore, 1993;Zalaquett & Chatters, 2012). Thus, identifying the components that promote a highquality relationship between school principals and counselors could significantly and positively impact these aforementioned facets of a school counselor's job.…”
Section: Principal-school Counselor Relationshipmentioning
confidence: 99%
“…Megan Kimber and Marilyn Campbell (2014) (in tandem with Cinotti, 2014;Hann-Morrison, 2011;Karatas & Kaya, 2015) postulated that the differences in the responsibilities between principals and other administrators compared to school counselors could add to some of the role stress experienced by school counselors. In particular, these researchers studied ethical dilemmas faced by principals and school counselors and reported that, although both parties approached dilemmas morally, they had a different viewpoint or perspective on whom they served (Kimber & Campbell, 2014). Principals and other administrators focused on the school as a whole, whereas school counselors tended to focus on individuals.…”
Section: The Conceptualization Of School Counselor Responsibilitymentioning
confidence: 99%
“…It is increasingly important to examine principals’ perceptions of school practices that have ethical meaning through a transnational perspective, since we are aware that ethics constitute an integral component of educational leadership (Gross and Shapiro, 2015; Hammersley-Fletcher, 2015; Kimber and Campbell, 2014). By learning from the successes and failures of others, by means of transnational studies in educational leadership, we can significantly improve comparable educational systems (Leithwood and Hallinger, 2012; Marfan and Pascual, 2018).…”
Section: Introductionmentioning
confidence: 99%